Induction of a rat model of premature ovarian insufficiency using D-galactose feeding during the critical periods of development: A pilot study - Marzieh Rostami Dovom; Mahsa Noroozzadeh; Nariman Mosaffa; Abbas Piryaei; Azita Zadevakili; Mohammad Amin Abdollahifar; Fahimeh Ramezani Tehrani (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Premature ovarian insufficiency (POI) affects about 1% of women of reproductive ages (15-45 yr), with no curative treatment. Objective: We aimed to present a rat model of POI using a D-galactose enriched diet. Materials and Methods: In a pilot study, 4 pregnant Wistar rats were divided into 4 groups; 3 groups were fed galactose-enriched diets at days 3-15 of pregnancy (G1); on the 3 rd day of pregnancy to parturition (G2), and the 3 rd day of pregnancy until the end of the weaning period (G3). Also, group 4, as the control group (G0), was fed standard pellets during the study. After confirming the lack of adverse effects of dieting with galactose in terms of offsprings' birth weight, we performed our study designed the same as the pilot study. A total of 40 pregnant Wistar rats were randomly divided into 4 groups. Ovarian histology, reproductive hormones, and immunological characteristics of the female offspring were examined in all experimental groups and compared. Results: The pilot study revealed no significant differences in the birth weight of the offspring of the 4 study groups (p = 0.96). The ovarian index in the female offspring of those with a gal-exposed diet was significantly lower than that of the control group offspring (p < 0.01). Conclusion: As the birth weights of the offspring of our experimental and control groups were similar, it can be concluded that the reduction of ovarian follicles after prenatal exposure to D-galactose is due to the ovotoxicity of galactose. The results of our final study will provide more information about the rat POI model induced by prenatal exposure to D-galactose.